What kept back on the mirror of COVID-19 related transverse myelitis? A genetic background! - Sinaei, Reza; Pezeshki, Sara; Sinaei, Roya (Iranian Journal of Child Neurology, 2023)
The acute transverse myelitis associated with COVID-19 cases have been reported worldwide. Nevertheless, Iran, Italy and USA are the most affected countries, witnessing the possibility that genetic factors might be associated with this susceptibility. The genetic variants of the coronavirus-2 entry mechanisms and host innate immune response related genes like interferons, interleukins, Toll-like receptors, human leukocyte antigen, blood groups, and some risk loci may be accountable. Here, we have a description of the compatibility of the geographical distribution between ATM and the Neanderthal core haplotype that confers risk for severe COVID-19, as well as some possible culprit genes.